Український фольклорист і етнограф Василь Бабенко - Ахатова, Ф. (Народна творчість та етнографія, 2005)
This is an artistic portrait of the Bashkirean ethnographer and professor of the Ufa Pedagogical Institute. His area of scientific interests are the studies of the life of Ukrainian minority in Bashkirya. He also the founder of the Filial of the Moscow Pedagogical University in Ufa. It is the only University in Russia were the teachers of Ukrainian language and literature are being prepared. In this University have being planned to create a methodological centre of the studies of history and culture of Slavs.